2007
DOI: 10.1158/1535-7163.mct-06-0503
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of topoisomerase IIα expression by a DNA sequence-specific polyamide

Abstract: Topoisomerase IIA (topo IIa) is an important target for several chemotherapeutic agents, including etoposide and doxorubicin. Confluent cells express low levels of topo IIa and are resistant to etoposide treatment. Repression of transcription in confluent cells is mediated by binding of the transcription factor NF-Y to inverted CCAAT motifs within the topo IIa promoter. To block the repressive binding of NF-Y, a polyamide (JH-37) was designed to bind to the flanking regions of selected CCAAT sites within the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…We recently showed that a polyamide directed against the binding site of NF-Y in the topo IIa promoter was able to inhibit NF-Y binding and alter gene expression in confluent cells (2). Other studies have shown that polyamides can modulate gene expression in vivo (24).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We recently showed that a polyamide directed against the binding site of NF-Y in the topo IIa promoter was able to inhibit NF-Y binding and alter gene expression in confluent cells (2). Other studies have shown that polyamides can modulate gene expression in vivo (24).…”
Section: Discussionmentioning
confidence: 99%
“…CaCo2 cells were also obtained from Cancer Research UK London Research Institute and grown in RPMI (Bioclear) supplemented with 10% FCS and 1% glutamine and incubated at 37jC in 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10,13) The hCTGF gene promoter contains several regulatory elements, such as Smad, AP1, TATA, NF-kB, GATA, CBP and Oct-1. [14][15][16][17] We designed a PI polyamide specific for bp Ϫ157 to Ϫ151 of the hCTGF promoter sequence.…”
Section: Discussionmentioning
confidence: 99%